Metastatic Infiltrating Ductal Carcinoma of the Breast to the Colon: A Case Report and Literature Review. (1st October 2013) - Samo, Salih; Sherid, Muhammed; Husein, Husein; Sulaiman, Samian; Brower, Jeffrey V.; Alper, Seth; Yungbluth, Margaret; Vainder, John A.
Abstract : True metastatic involvement of the colon is rare. Colonic metastases occur most commonly secondary to peritoneal metastases from intra-abdominal malignancies. Breast cancer is the most common malignancy that metastasizes hematogenously to the colon. Colonic metastatic disease mimics primary colonic tumors in its presentation. Colonic metastatic involvement is a poor prognostic sign, and the pathologist should be informed about the history of the primary breast cancer when examining the pathologic specimens. In this paper, we report a case of an ileocecal mass found to be histologically consistent with metastatic ductal breast cancer, and then we review the literature about breast cancer metastases to the gastrointestinal tract in general and colon in particular.